New Guidance for an Old Problem: Early Release for Seriously Ill and Elderly Prisoners in Europe. (March 2017) - Handtke, Violet; Wangmo, Tenzin; Elger, Bernice; Bretschneider, Wiebke
Early release of seriously ill and elderly prisoners is possible in several countries, but only few prisoners gain such exemption. We identified hurdles to the implementation of early release laws in Europe by analyzing legal requirements for such release and with 40 stakeholder qualitative interviews. Provisions are based on prisoners' health status and the ability to care for them in prison. Interviews revealed three barriers: practical hurdles, penological goals, and multiple interests. Finally, early release is obstructed because three justifications are often confounded: compassion, the principle of equivalence, and practical concerns, such as costs and overcrowding.